News Briefs. - Garber, Lee (Computer (00189162), 2014)
Topics include ongoing problems caused by the Heartbleed Internet-security flaw, the end of another epic Apple-Samsung patent-related trial, an Internet Explorer bug threatening users of the world's most popular browser, new laser technology that could quadruple Internet-access speeds, Facebook working on drones and satellites to bring the Internet to remote areas, a US government report that says the Internet of Things could threaten privacy, scientists developing robots that can each other robots to play games, governments paying Microsoft to keep supporting Windows XP, a researcher showing that hackers could attack networked traffic-control equipment and cause gridlock, and police beginning to crowdsource their investigation.